A Comparative Study of Security in E-commerce: Review - Chatterjee, Sumanta; Gupta, Krishnayan (International Journal of Computer Sciences and Engineering, 2025)
The goal of e-commerce system is to provide secure connections between customers and the company with other parties acquiring personal information. But in the various stages of e-commerce an individual or company is a victim of unwanted attacks or threats. Here, the investigation is done on the security concerns among different e-commerce websites. Matters such as privacy, security and threats, impersonation, forged identity etc. is also looked upon. The different threats are brought forward with maximum efforts done onto how it can be reduced.